Does atomoxetine improve executive function, inhibitory control, and hyperactivity?: results from a placebo-controlled trial using quantitative measurement technology - Wehmeier, Peter M.; Dittmann, Ralf; Banaschewski, Tobias (Journal of clinical psychopharmacology, 2012)
The primary objective of this study was to evaluate the efficacy of atomoxetine (ATX) on attention-deficit/hyperactivity disorder (ADHD)-related symptoms assessed as standard variables of a computer-based continuous performance test (cb-CPT) combined with a motion-tracking (MT) device. This was a 2-arm, 8-week, randomized, double-blind, placebo-controlled study in patients with ADHD (6-12 years). Therapy with ATX started with 0.5 mg/kg per day for 1 week, followed by 7 weeks on the target dosage of 1.2 mg/kg per day. Primary outcomes were cb-CPT/MT standard scores after 8 weeks using mixed models for repeated measurements. In addition, investigator-rated ADHD Rating Scale (ADHD-RS), Weekly Ratings of Evening and Morning Behavior (WREMB), and Clinical Global Impression - Severity-ADHD (CGI-S-ADHD) scores were assessed. Of 128 patients randomized, 125 were evaluated (ATX/placebo: 63/62). Baseline characteristics were comparable in both groups (overall, 80.2% boys; mean [SD] age, 9.0 [1.79] years; comorbid Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition diagnosis, 40.0% oppositional defiant disorder/conduct disorder; prior stimulant treatment, 24.8%; ADHD-RS total score, 36.99 [11.56]). At week 8, all cb-CPT/MT q-scores were significantly reduced versus placebo (all P < 0.001) with effect sizes (ESs) of reaction time (RT) variation (ES = 0.71), mean RT (ES = 0.41), number of microevents (ES = 1.00), commission error rate (ES = 0.50), distance of movement (ES = 0.90), area of movement (ES = 1.08), omission error rate (ES = 0.70), time active (ES = 0.69), motion simplicity (ES = 0.38), and normalized variance of RT (ES = 0.50). Secondary end points also improved significantly in favor of ATX: ADHD-RS (total score ES = 1.30, P < 0.001; hyperactivity/impulsivity subscore ES = 1.37, P < 0.001; inattention subscore ES = 1.07, P < 0.001), WREMB (total score ES = 1.00, P < 0.001; morning subscore ES = 0.59, P = 0.002; evening subscore ES = 1.02, P < 0.001), CGI-S-ADHD (ES = 1.11, P < 0.001). The results of this study show that ATX for 8 weeks significantly reduced ADHD-related symptoms as measured by the cb-CPT/MT.
Gesehen am 28.08.2018